Purchase Decisions for Victory One Racing Motorcycle Variations in Surabaya - Muhammad Faiz Athoillah; Arasy Alimudin; Ani Wulandari (NAROTAMA UNIVERSITY, Indonesia, 2021)
This study aims to determine the analysis of the influence of electronic word of mouth, discounts, and social media advertisements either simultaneously or partially on the purchasing decisions of the Victory Onr Racing motorcycle variation product in Surabaya. This research is a quantitative research. The population of this study are consumers who use the product victory one racing in Surabaya. The sampling technique used was purposive sampling (respondents based on predetermined criteria), with a total of 97 people as samples. The data collection technique used is a questionnaire, and the data analysis technique used is multiple linear regression analysis with the help of the SPSS program. The results show that, the significant probability number of E-WoM (0.043) < (0.05) so that the E-WoM variable has a significant influence on purchasing decisions, the significant probability of Discount (0.023) < (0.05) so that the Discount variable has a significant influence on purchasing decisions, the probability number is significant for social media advertising (0.003) < (0.05) so that the social media advertising variable has a significant influence on purchasing decisions. This means that the variables of E-Wom, Discounts, and Social Media Advertising partially have a significant effect on purchasing decisions.electronic word of mouth